Work Effectiveness and Discipline Affect Organizational Performance Achievement at Ornamental Fish Cultivation Research Center (BRBIH – KKP) - Hidayat, Nur Arief; Syamsunasir, Syamsunasir (Dinasti Publisher, 2025)
Work effectiveness and discipline affect organizational performance achievement. This study aims to determine and examine the effect of work effectiveness with Work Discipline on the performance goals of an organization. This research provides an overview and approach to the organization to optimize Standard Operating Procedures in work effectiveness and discipline in order to achieve the expected performance targets and output. The performance goals of an organization are the main indicator of the progress of an organization so that achievements and rewards are obtained. Meanwhile, downgrading and punishment can provide a warning that an organization is indicated to be not good. This research uses qualitative research methods. This research focuses on in-depth observation to understand the phenomena experienced by the research subject. The population in this study were all employees of the Ornamental Fish Cultivation Research Center. This study consisted of 60 employees. It is hoped that this research will produce a clear picture of the importance of effectiveness and work discipline in building a structured system and building solid cooperation. the results are expected, with discipline and work effectiveness, the goals in the service that have been set, will be achieved optimally and maximally. main performance target indicators achieved, giving a positive impression.